A relação entre a auto-eficácia em tecnologia da informação, o capital social e o compartilhamento do conhecimento - Marchiori, Rejane Werlang (2023)
The use of technological resources enables multiple forms of communication and interaction in the organizational environment. In this regard, knowledge sharing, recognized as a crucial process for knowledge management, can be enhanced through the systematic use of these resources. Thus, the present study aimed to identify the role of information technology self-efficacy and social capital constructs, using the perspectives of social capital and cognitive social theory, in tacit knowledge sharing. Regarding the methods and procedures, the research employed a quantitative approach, with data collection carried out through a questionnaire directed at employees of the studied organization, processed using partial least squares structural equation modeling (PLS-SEM) via SmartPLS 4 software. The results demonstrated significant, direct, and positive effects of structural social capital, cognitive social capital, and information technology selfefficacy on tacit knowledge sharing. Furthermore, the study revealed an innovative finding: the moderating effect of information technology self-efficacy on the relationship between structural social capital and knowledge sharing. The findings reinforced the antecedents of tacit knowledge sharing, emphasizing the importance of structural and cognitive dimensions of social capital. From a practical perspective, the results indicated that enhancing employees' trust and technological competence can improve processes of tacit knowledge sharing. Additionally, organizations can enhance their knowledge sharing processes by fostering opportunities for social interaction and promoting shared vision and language among employees.